Effect of drying on the cyanide content and its toxicity in seeds of Hevea brasiliensis - Okafor P N; Njoku O U; Okorie U (Natural Rubber Research, 2005)
Over drying of shelled whole seeds of Hevea brasiliensis at 60-180 degree C over 30 to 180 min resulted in reduction (8.5 to 43.63;) in cyanide content. Drying of chipped seeds was more effective. Rats fed with feed formulation containing such processed rubber seed kernels did not show any toxicity symptoms although there was increase in cyanide and thiocyanate in the blood serum and urine.
Keywords: Animal feed; Cyanide toxicity; Rubber seed